A multicenter evaluation of pandemic influenza A/H1N1 in hematopoietic stem cell transplant recipients. Issue 5 (25th July 2013) - Reid, G.; Huprikar, S.; Patel, G.; Razonable, R.R.; Mossad, S.; Levi, M.; Gregg, K.; Shoham, S.; Humar, A.; Adams, W.; Kumar, D.; ,
Abstract: Background: Hematopoietic stem cell transplant (HSCT) recipients have increased morbidity from respiratory viral infections. Pandemic influenza A – A(H1N1)/pdm09 – in 2009–2010 was associated with increased severity of illness in patients with underlying co‐morbidities including HSCT, but the factors that contribute to severe disease in HSCT patients are not well characterized. Methods: We conducted a multicenter review of microbiologically proven influenza A(H1N1)pdm09 in the HSCT population between April 2009 and April 2010 to determine factors that are associated with severe disease. Results: We identified 37 adult patients (26 allogeneic and 11 autologous HSCT recipients). Median time from transplant to diagnosis was 411 days (range 4 days–14.9 years). Three cases were hospital acquired. Twenty‐eight of 37 (75.7%) had confirmed A(H1N1)pdm09. Presumed viral lower respiratory tract infection was present in 12/37 (32.4%) patients. Antiviral therapy was given to 33/37 (89%) patients, primarily oseltamivir ( n = 24) and oseltamivir before or after another antiviral ( n = 8). Excluding those with nosocomial A(H1N1)pdm09, 18/34 (52.9%) were hospitalized and 6 (33%) required admission to an intensive care unit. Mortality within 30 and 60 days of symptom onset was 7/37 (18.9%) and 11/37 (29.7%), respectively. Factors associated with mortality included nosocomial acquisition ( P = 0.023), receipt of mycophenolate mofetil ( P = 0.001), or antilymphocyte antibody ( P = 0.005) within the past 6 months, reduced‐intensity conditioning ( P = 0.027), and bacteremia ( P = 0.021). Conclusions: A(H1N1)pdm09 infection was particularly severe in HSCT recipients, specifically among those receiving augmented immunosuppression for graft‐versus‐host disease. The high mortality of the nosocomial cases highlights the need for strict infection‐control measures in hospitals during influenza outbreaks.